CITES DAN KERJA SAMA INTERNASIONAL PENANGANAN PERDAGANGAN SATWA LIAR - Jaslim, Rio Syahrial (UI Scholars Hub, 2004)
This article generally discusses the regime of CITES and how it managed international cooperation on handling the wildlife trade since its entry had come into force. The article then attempts to define the dynamics of wildlife trade issues, particularly those dealing with legal problem at the level of international system, to answer these following questions: How was CITES convention being implemented, and what are the barriers that should be overcome by international cooperation to handle wildlife trade by using environmental regimes?